Body image in and out of the lab: Correspondence between lab-based attentional bias data and body shape dissatisfaction experiences in daily life. (March 2020) - Fuller-Tyszkiewicz, Matthew; Vuong, Hao; Linardon, Jake; Krug, Isabel; Broadbent, Jaclyn; Rodgers, Rachel F.
Highlights: We explored trait body dissatisfaction (BD), attentional biases, and state BD in daily life. Bias towards thin body images and trait BD were both linked to state BD. This bias and elevated trait BD were associated with smaller reductions in state BD once initiated in daily life. Delayed disengagement from thin body images was linked to greater reductions in state BD. Abstract: Accumulating lab-based studies have identified attentional biases in processing of negative appearance-related information among individuals with elevated trait body shape and weight dissatisfaction (BD). How these biases translate into experiences of BD in daily life remains unclear and, hence, was the focus of the present study. Thirty-eight women aged between 18–40 years completed a baseline survey and modified dot-probe task with both fat and thin appearance-related stimuli in a laboratory setting. Participants also downloaded a smartphone app that prompted them 10 times per day for 7 days to rate current body dissatisfaction. Results revealed that heightened BD in daily life tended to be transitory, and followed by a substantially lower rating of BD by the next survey (∼1−2 h later). For individuals with elevated trait BD and facilitated attention towards thin body images, this reduction in state BD was more gradual. Surprisingly, delayed disengagement towards thin body images was associated with greater reduction in state BD. Consistent with the hypothesis, moderating effects were not observed when initial state BD level was low. Susceptibility for immediate, short-term attentional biases towards appearance-related information may be a vulnerability factor for the prolonged persistence of negative body image experiences in daily life.